2020
DOI: 10.1109/jstars.2020.3002777
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Ocean Tidal Loading in InSAR Measurements Determined by Kinematic PPP Solutions of a Regional GPS Network

Abstract: The coastal crustal deformation caused by ocean tidal loading (OTL) varies spatially and temporally, and this spatiotemporal variation in satellite-based interferometric synthetic aperture radar (InSAR) measurements needs to be determined. In this paper, we propose a spatiotemporal modeling method to estimate the OTL displacements in InSAR measurements using the kinematic precise point positioning (PPP) solutions of a regional GPS network. We tested the method through an experiment using 25 Sentinel-1B images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We evaluated the ground tidal displacement in the long-strip differential interferogram based on the tidal estimation of the GPS continuous reference station network and the tidal model. For inland areas more than 200 km away from the coastline of the west coast of the U.S., the error produced by bilinear ramp fitting is much less than in coastal areas, which has limited influence on the studies of InSAR ground deformation monitoring; For most coastal areas, there is little difference between the traditional ocean tide model and PPP tidal displacements, and previous studies have proved the OTL displacements in the InSAR measurements can be corrected based on a global ocean tide model [12,13]. However, Figure 4 and Abbaszadeh et al both indicated that in some localized coastal areas, such as Area A, the maximum StdDev differences between the tidal constituents' displacement time series of recent global ocean tide models are 1~2 mm [22], which may be introduced tidal displacement residuals into the OTL correction of the InSAR ground deformation measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the ground tidal displacement in the long-strip differential interferogram based on the tidal estimation of the GPS continuous reference station network and the tidal model. For inland areas more than 200 km away from the coastline of the west coast of the U.S., the error produced by bilinear ramp fitting is much less than in coastal areas, which has limited influence on the studies of InSAR ground deformation monitoring; For most coastal areas, there is little difference between the traditional ocean tide model and PPP tidal displacements, and previous studies have proved the OTL displacements in the InSAR measurements can be corrected based on a global ocean tide model [12,13]. However, Figure 4 and Abbaszadeh et al both indicated that in some localized coastal areas, such as Area A, the maximum StdDev differences between the tidal constituents' displacement time series of recent global ocean tide models are 1~2 mm [22], which may be introduced tidal displacement residuals into the OTL correction of the InSAR ground deformation measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The global OTL displacements are usually calculated using an ocean tidal model-based loading Green's function method. Taking the FES2014b model as an example, the up (U), north (N) and east (E) OTL displacements d OTL n,p of point p with an interval of 300 s in the year 2019 can be obtained by using the ocean tidal model-based loading Green function method, and the variation of the OTL displacements in three-dimension is evaluated by the standard deviation (StdDev) S OTL p , which can be expressed as [12]:…”
Section: Tidal Data Analysis and Processingmentioning
confidence: 99%
See 1 more Smart Citation